Risk factors associated with overweight and obesity among female Mexican teenagers - María Concepción Medina-Zacarías; Teresa Shamah-Levy; Lucía Cuevas-Nasu; Ignacio Méndez Gómez-Humarán; Sonia Lizeth Hernández-Cordero (Salud Pública de México, 2020)
Objective. To analyze risk factors associated with overweight and obesity (OW+O) among female Mexican teenagers (12 to 19 years old). Materials and methods. Secondary analysis of 1 072 teenagers from the Halfway National Survey of Health and Nutrition (Ensanut MC, 2016). Ordinal logistic regression models were used to estimate the association between OW+O and screen time, living with adults with OW+O, marital union, and dietary patterns, among others. Results. OW+O in adolescents was higher when living with overweighed and obese adults (OR= 2.13), >2 hours of screen time (OR= 2.5), discretionary food consumption pattern (OR= 1.81), living in marital union (OR = 2.13), classified in the highest tertile of household wealth index (OR= 1.86), work and doing housework (OR= 5.4). Conclusions. The most important risk factors associated with OW+O in Mexican teenagers were related to family factors and lifestyles.